(untitled) - Fuller, Joanna Kotcher (Philadelphia, 2013)
Using a detailed, heavily illustrated, step-by-step approach, this guide helps you master the fundamentals and procedures of restorative and preventive dentistry and learn to make informed decisions to solve patient needs. It draws from both theory and practice, and is supported by extensive clinical and laboratory research.
Keywords: Kỹ thuật viên phòng phẫu thuật,Phòng điều dưỡng,Operating room nursing,Operating room technicians